Adaptive changes of sediment microbial communities associated with cleanup of oil spills in Nigerian mangrove forests. (March 2022) - Iturbe-Espinoza, Paul; Bonte, Matthijs; Gundlach, Erich; Brandt, Bernd W.; Braster, Martin; van Spanning, Rob J.M.
Abstract: The objectives of this study were to assess the influence on microbial communities resulting from i) the physical removal of free oil (pre-treatment or post-treatment), and ii) the level of oiling within a contaminated former mangrove forest. Sediment samples were collected before and after the removal of free oil. Before the process of remediation, a highly biodiverse mangrove microbiome which had adapted to history of recurring oil spills was observed. After removing the surface oil, the microbial diversity of the sediments reduced, with members of the phyla Firmicutes and Proteobacteria becoming dominant. This indicates that while water flushing reduced overall microbial diversity, it stimulated the growth of a more specialized bacterial community reported to be involved in hydrocarbon biodegradation. These results provide new insights on microbial communities and their succession in mangrove forest sediments, that will be useful for monitoring oil cleaning programs using water flushing to remove free oil. Highlights: Soil microbial communities play a key role in the natural attenuation of oil spills. Water flushing influences communities with a selection of specialized bacteria. The gradient of oil did not explain the differences in microbial community structures. The microbial profiles cluster according to spill and treatment stages.